The Impact of Family Engagement on Student Achievement - Christina M Hall (Networks: An Online Journal for Teacher Research, 2020)
This action research study explores the impact of family engagement on student achievement using three family/student pairs. Family involvement has an impact on student learning and achievement throughout the school year. Taking a look at how a family’s involvement in their student’s learning plays a part on the achievement the student has throughout the school year. Previous writing scores were used to compare the growth made within a three-month period after the families worked with students to give feedback through a classroom communication app. Families were able to work at home to give feedback while their students were in class for quick response time and authenticity. The teacher/researcher coached families on how to give accurate feedback that would help students grow and feel successful.
Keywords: Family involvement; family engagement; writing; student feedback